2021
DOI: 10.1002/jcu.23027
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Chorionic bump detected in the third trimester

Abstract: A chorionic bump (CB) is a focal irregular bulge in the surrounding choriodecidual due to hematoma. The incidence of CB is between 1.5 and 7 per 1000 pregnancies. The presence of a chorionic bump is associated with a significantly higher risk of adverse perinatal outcomes. CB often decreases in size with time and rarely persists beyond the first trimester. Our case report presents and discusses a chorionic bump diagnosed in the third trimester. To our knowledge, this is the first case of CB to reported in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, the majority of cases involving CB disappear in the second trimester, which is consistent with the findings of earlier researches [1,2,3,4] , and raises the notion that the body can reabsorb the underlying hematoma. Fang, Yunjing, et al's findings differ from those of Hisham M. et al, who reported CB in the third trimester that continues to report a CB until delivery [11,12] .…”
Section: Discussionmentioning
confidence: 61%
“…However, the majority of cases involving CB disappear in the second trimester, which is consistent with the findings of earlier researches [1,2,3,4] , and raises the notion that the body can reabsorb the underlying hematoma. Fang, Yunjing, et al's findings differ from those of Hisham M. et al, who reported CB in the third trimester that continues to report a CB until delivery [11,12] .…”
Section: Discussionmentioning
confidence: 61%
“…Fo r these reasons, def initive surgical treatment with dilation and curettage was decided, sending the tissue collected f rom the curettage procedure f or complementary histopathological study. It was expected that the results would show sections or cystic-based areas in the histopathological study with the possibility of f inding f ibrin tissue and/or scattered chorionic villi covered by cytotrophoblasts and syncytiotrophoblasts, as has been seen in other publications (10) . However, in our histopathological analysis report, it showed: abundant ovulodecidual remains, various f ragments of irregular tissue which together measure 7x4.5x2cm, with areas of a light brown membranous appearance, alternating areas of a hairy, light and dark brown appearance, the tissue presents data of non-specific moderate acute deciduitis with f ocal microabscess in addition to f irst trimester chorionic villi and Arias-Stella reaction.…”
Section: Clinical Casementioning
confidence: 66%
“…However, adequate surveillance should be carried out in this type of case, since some authors have postulated that large subamniotic hematomas may be associated with fetal growth restriction and/or early embryonic death (6) . An additional associated risk is related to its location; if they are close to the umbilical cord insertion site, and especially if they are large, they can compress the placental vessels and the umbilical cord, leading to adverse f etal outcome (10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation